Design and vibration analysis of a self-adaptive piston in a novel nanoimprint system. Issue 4 (10th July 2017) - Liu, Chaoran; Su, Yufeng; Yue, Jinzhao; Wang, Junjie; Xia, Weiwei; Li, Dongxue; Wang, Wen; Wang, Pan; Duan, Zhiyong
Abstract : Purpose: A self-adaptive piston is designed for the compressional gas cushion press nanoimprint lithography system. It avoids the lube pollution and high wear of traditional piston. Design/methodology/approach: The self-adaptive piston device consists of symmetrical piston bodies, piston rings and other parts. The two piston bodies are linked by a ball-screw. The locking nut adjusts the distance between two piston bodies to avoid the piston rings from being stuck. The piston rings are placed between two piston bodies. Findings: The simulation results based on COMSOL indicate that cylinder vibration caused by self-adaptive piston is 15.9 times smaller than the one caused by a traditional piston. Originality/value: The self-adaptive piston is superior to the traditional piston in decreasing cylinder vibration.